Identifying the Ukrainian: Marina Lewycka’s “A Short History of Tractors in Ukrainian” - Weretiuk, Oksana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
This essay deals with the problem of Ukrainian identity in Marina Lewycka’s novel: “A Short History of Tractors in Ukrainian” (2005). The paper suggests a twofold imagological1 analysis in order to answer how the second generation of Ukrainian immigrants in Great Britain (children of the post-WWII political migration) perceives, the Ukrainian newcomer, the economic immigrant from a post-communist state, who looks strange and other for them and how the reader, in his turn, perceives the Ukrainianness of the first and the second. It also underlines that Marina Lewycka infuses the Ukrainian history (past and modern) with a unique sense of humour based on cultural varieties. Her English-Ukrainian and Ukrainian-English characters are observed from different perspectives.
Keywords: imagological analysis; Ukrainian migration in Great Britain; Ukrainian history; postcommunism; assimilation